Tataan Tektonika Batuan Gunung Api di Komplek Adang Kabupaten Mamuju Provinsi Sulawesi Barat - Sukadana, I Gde; Harijoko, Agung; Setijadji, Lucas Donny (EKSPLORIUM, 2015)
Adang volcanic complexlocated in Mamuju Region, West Sulawesi can be grouped more detail into seven complexes that are Tapalang, Ampalas, Adang, Malunda, Karampuang, Sumare, and Labuan Rano. Adang complex is one of the main volcanic complexes that still can be identified with good morphological formations. This complex is composed of alkaline volcanic rocks with basic to intermediates composition that have high value of radiation dose rate caused by their radioactive mineral content. Radioactive mineral occurrences on the basaltic-andesitic rocks has never been found in Indonesia, so it becomes very interesting to do research mainly tectonic settings of the volcanic rock complex formation. The purpose of this study is to determine magmatiic typology related with the tectonic setting based on volcanic rock geochemistry using X-Ray Fluorences (XRF) analysis. Adang volcanic rock is the result of a complex process of volcanism having a volcanic center and several lava domes. They are composed of phonolite to dacite rock, with ultrapotassic affinity, interpretation of data concluded that tectonic setting of magmatism formed in active continental margin (ACM). Magmatism source from vulcanic activities influenced by South WestSulawesi micro-continental crust.